Ag-Ni bimetallic film on CaF2 prism for high sensitive surface plasmon resonance sensor - Nisha, Ananthan; Maheswari, Pandaram; Subanya, Santhanakumar; Anbarasan, Ponnusamy Munusamy; Rajesh, Karuppaiya Balasundaram; Jaroszewicz, Zbigniew (Photonics Letters of Poland, 2021)
We present a surface plasmon resonance (SPR) structure based on Kretschmann configuration incorporating bimetallic layers of noble (Ag) and magnetic materials (Ni) over CaF2 prism. Extensive numerical analysis based on transfer matrix theory has been performed to characterize the sensor response considering sensitivity, full width at half maxima, and minimum reflection. Notably, the proposed structure, upon suitably optimizing the thickness of bimetallic layer provides consistent enhancement of sensitivity over other competitive SPR structures. Hence we believe that this proposed SPR sensor could find the new platform for the medical diagnosis, chemical examination and biological detection. Full Text: PDF References J. Homola, S.S. Yee, G. Gauglitz, "Surface plasmon resonance sensor based on planar light pipe: theoretical optimization analysis", Sens. Actuators B Chem. 54, 3 (1999). CrossRef X.D. Hoa, A.G. Kirk, M. Tabrizian, "Towards integrated and sensitive surface plasmon resonance biosensors: A review of recent progress", Bioelectron, 23, 151 (2007). CrossRef Z. Lin, L. Jiang, L. Wu, J. Guo, X. Dai, Y. Xiang, D. Fan, "Tuning and Sensitivity Enhancement of Surface Plasmon Resonance Biosensor With Graphene Covered Au-MoS 2-Au Films", IEEE Photonics J. 8(6), 4803308 (2016). CrossRef T. Srivastava, R. Jha, R. Das, "High-Performance Bimetallic SPR Sensor Based on Periodic-Multilayer-Waveguides", IEEE Photonics Technol. Lett. 23(20), 1448 (2011). CrossRef P.K. Maharana, R. Jha, "Chalcogenide prism and graphene multilayer based surface plasmon resonance affinity biosensor for high performance", Sens. Actuators B Chem. 169, 161 (2012). CrossRef R. Verma, B.D. Gupta, R. Jha, "Sensitivity enhancement of a surface plasmon resonance based biomolecules sensor using graphene and silicon layers", Sens. Actuators B Chem. 160, 623 (2011). CrossRef I. Pockrand, "Surface plasma oscillations at silver surfaces with thin transparent and absorbing coatings", Surf. Sci. 72, 577 (1978). CrossRef R. Jha, A. Sharma, "High-performance sensor based on surface plasmon resonance with chalcogenide prism and aluminum for detection in infrared", Opt. Lett. 34(6), 749 (2009). CrossRef E.V. Alieva, V.N. Konopsky, "Biosensor based on surface plasmon interferometry independent on variations of liquid’s refraction index", Sens. Actuators B Chem. 99, 90 (2004). CrossRef S.A. Zynio, A. Samoylov, E. Surovtseva, V. Mirsky, Y. Shirshov, "Bimetallic Layers Increase Sensitivity of Affinity Sensors Based on Surface Plasmon Resonance", Sensors 2, 62 (2002). CrossRef S.Y. Wu, H.P. Ho, "Sensitivity improvement of the surface plasmon resonance optical sensor by using a gold-silver transducing layer", Proceedings IEEE Hong Kong Electron Devices Meeting 63 (2002). CrossRef B.H. Ong, X. Yuan, S. Tjin, J. Zhang, H. Ng, "Optimised film thickness for maximum evanescent field enhancement of a bimetallic film surface plasmon resonance biosensor", Sens. Actuators B Chem. 114, 1028 (2006). CrossRef B.H. Ong, X. Yuan, Y. Tan, R. Irawan, X. Fang, L. Zhang, S. Tjin, "Two-layered metallic film-induced surface plasmon polariton for fluorescence emission enhancement in on-chip waveguide", Lab Chip 7, 506 (2007). CrossRef X. Yuan, B. Ong, Y. Tan, D. Zhang, R. Irawan, S. Tjin, "Sensitivity–stability-optimized surface plasmon resonance sensing with double metal layers", J. Opt. A: Pure Appl. Opt. 8, 959, (2006). CrossRef M. Ghorbanpour, "A novel method for the production of highly adherent Au layers on glass substrates used in surface plasmon resonance analysis: substitution of Cr or Ti intermediate layers with Ag layer followed by an optimal annealing treatment", J. Nanostruct, 3, 309, (2013). CrossRef Y. Chen, R.S. Zheng, D.G. Zhang, Y.H. Lu, P. Wang, H. Ming, Z.F. Luo, Q. Kan, "Bimetallic chips for a surface plasmon resonance instrument", Appl. Opt. 50, 387 (2011). CrossRef N.H.T. Tran, B.T. Phan, W.J. Yoon, S. Khym, H. Ju, "Dielectric Metal-Based Multilayers for Surface Plasmon Resonance with Enhanced Quality Factor of the Plasmonic Waves", J. Electron. Mater. 46, 3654 (2017). CrossRef D. Nesterenko Z. Sekkat, "Resolution Estimation of the Au, Ag, Cu, and Al Single- and Double-Layer Surface Plasmon Sensors in the Ultraviolet, Visible, and Infrared Regions", Plasmonics 8, 1585 (2013). CrossRef M.A. Ordal, R.J. Bell, R.W. Alexander, L.L. Long, M.R. Querry, "Optical properties of fourteen metals in the infrared and far infrared: Al, Co, Cu, Au, Fe, Pb, Mo, Ni, Pd, Pt, Ag, Ti, V, and W.", Appl. Opt. 24, 4493 (1985). CrossRef H. Ehrenreich, H.R. Philipp, D.J. Olechna, "Optical Properties and Fermi Surface of Nickel", Phys. Rev. 31, 2469 (1963). CrossRef S. Shukla, N.K. Sharma, V. Sajal, "Theoretical Study of Surface Plasmon Resonance-based Fiber Optic Sensor Utilizing Cobalt and Nickel Films", Braz. J. Phys. 46, 288 (2016). CrossRef K. Shah, N.K. Sharma, AIP Conf. Proc. 2009, 020040 (2018). [23] G. AlaguVibisha, Jeeban Kumar Nayak, P. Maheswari, N. Priyadharsini, A. Nisha, Z. Jaroszewicz, K.B. Rajesh, "Sensitivity enhancement of surface plasmon resonance sensor using hybrid configuration of 2D materials over bimetallic layer of Cu–Ni", Opt. Commun. 463, 125337 (2020). CrossRef A. Nisha, P. Maheswari, P.M. Anbarasan, K.B. Rajesh, Z. Jaroszewicz, "Sensitivity enhancement of surface plasmon resonance sensor with 2D material covered noble and magnetic material (Ni)", Opt. Quantum Electron. 51, 19 (2019). CrossRef M.H.H. Hasib, J.N. Nur, C. Rizal, K.N. Shushama, "Improved Transition Metal Dichalcogenides-Based Surface Plasmon Resonance Biosensors", Condens.Matter 4, 49, (2019). CrossRef S. Herminjard, L. Sirigu, H. P. Herzig, E. Studemann, A. Crottini, J.P. Pellaux, T. Gresch, M. Fischer, J. Faist, "Surface Plasmon Resonance sensor showing enhanced sensitivity for CO2 detection in the mid-infrared range", Opt. Express 17, 293 (2009). CrossRef M. Wang, Y. Huo, S. Jiang, C. Zhang, C. Yang,T. Ning, X. Liu, C Li, W. Zhanga, B. Mana, "Theoretical design of a surface plasmon resonance sensor with high sensitivity and high resolution based on graphene–WS2 hybrid nanostructures and Au–Ag bimetallic film", RSC Adv. 7, 47177 (2017). CrossRef P.K. Maharana, P. Padhy, R. Jha, "On the Field Enhancement and Performance of an Ultra-Stable SPR Biosensor Based on Graphene", IEEE Photonics Technol. Lett. 25, 2156 (2013). CrossRef